Ascending aorta mycotic aneurysm in a child secondary to subacute infective endocarditis on the basis of congenital aortic stenosis demonstrated by cardiac computerized tomography. Issue 3 (21st January 2021) - Gemalmaz, Hüseyin; Tok, Özge Ö.; Bingöl, Gülsüm; Bakan, Selim; Sari, Ibrahim; Korkmaz, Ali A.
Abstract: Infective endocarditis (IE) is rarely seen in children, and it can cause significant morbidity and mortality. Congenital heart disease is a predisposing cardiac condition for IE and has an increasing prevalence. A mycotic aortic aneurysm is a rare disease due to infection and it has been reported that it may be a result of IE. We present a 10‐year‐old boy who was referred to our cardiovascular surgery department due to severe aortic stenosis (AS). Transthoracic echocardiography revealed calcific severe AS and computerized tomography (CT) angiography was performed to better evaluate the ascending aorta. CT angiography demonstrated a saccular aneurysm of the ascending aorta. The underlying pathology was considered as chronic IE on top of congenital AS with an unknown number of cusps. Histologic findings supported our diagnosis and accompanied by a saccular aneurysm. The patient underwent a successful aortic root enlargement, mechanical aortic valve replacement, and ascending aorta repair surgery.